Preliminary Assessment of Bovine Tuberculosis at the Livestock/Wildlife Interface in two Protected Areas of Northern Botswana. (31st October 2013) - Jori, F.; Mokospasetso, M.; Etter, E.; Munstermann, S.; Newman, S. H.; Michel, A.
Summary: Protected areas of northern Botswana such as the Okavango Delta (OD) or Chobe National Park (CNP) are well‐known hot spots for the conservation of African wildlife. However, their infection status regarding bovine tuberculosis (BTB) at the domestic/wildlife interface has never been investigated. To provide preliminary baseline data on the circulation of Mycobacterium bovis in those sites, we performed a cross‐sectional survey on 130 buffalo in both protected areas (60 individuals from CNP and 70 from OD) and 818 cattle in their surrounding communal lands (369 in CNP and 449 in the OD). Whole‐blood samples were tested using a commercial interferon‐gamma assay (IFN‐γ) with modifications. The apparent BTB prevalence in buffalo was nil in CNP and 0.7% 95% CI [0.2–1.9] in the OD, while the apparent BTB prevalence in cattle was 0.7% 95% CI [0.2–2.1] in the OD and 2.4% 95% CI [1.2–4.7] in CNP. True prevalence values calculated on the basis of the locally applicable IFN‐γ test performance suggested that BTB prevalence was nil in both buffalo populations and in cattle from the OD interface, but reached 2.3% 95% CI [0.2–4.5] in cattle populations around CNP. The results of a questionnaire survey conducted among a sample of farmers living in the communities adjacent to each conservation area (97 and 38 persons in the OD and CNP, respectively) suggested a higher risk of the circulation of M. bovis at the wildlife/livestock interface of the CNP than at that of the OD. However, further comprehensive studies are needed to confirm the circulation of M. bovis and to monitor the inter‐species and transboundary transmission of BTB in northern Botswana.